Results from the intercalibration of optical low-light calibration sources 2011 - Brändström, B. Urban E.; Enell, Carl-Fredrik; Widell, Ola; Hansson, Thord; Whiter, Daniel; Mäkinen, Sanna; Mikhaylova, Daria; Axelsson, Katarina; Sigernes, Fred; Gulbrandsen, Njål; Schlatter, Nicola M.; Gjendem, Amund Gjerde; et al. (Copernicus GmbH, 2011)
Abstract. Following the 38th Annual Meeting on Atmospheric studies by Optical methods at Siuntio in Finland, an intercalibration workshop for optical low-light calibration sources was held in Sodankylä, Finland. The main purpose of this workshop was to provide a comparable scale for absolute measurements of aurora and airglow. All sources brought to the intercalibration workshop were compared to an international standard source (Fritz-Peak) using the Lindau Calibration Photometer built by Wilhelm Barke and Hans Lauche in 1984. The international standard source is on loan from Michael Gadsden, Aberdeen. The results were compared to several earlier intercalibration workshops. It was found that most sources were fairly stable over time with errors in the range of 5–20%. To further validate the results, two sources were also intercalibrated at UNIS, Longyearbyen, Svalbard. Preliminary analysis indicate good agreement with the intercalibration in Sodankylä.